2004
DOI: 10.1002/chin.200442221
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Acylated Quercetin Tetraglycoside from Oolong Tea (Camelia sinensis) extracts.

Abstract: A Novel Acylated Quercetin Tetraglycoside from Oolong Tea (Camelia sinensis) extracts. -(MIHARA, R.; MITSUNAGA*, T.; FUKUI, Y.; NAKAI, M.; YAMAJI, N.; SHIBATA, H.; Tetrahedron Lett. 45 (2004) 26, 5077-5080; Fac. Bioresour., Mie Univ., Tsu, Mie 514, Japan; Eng.) -Mais 42-221

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 1 publication
1
8
0
1
Order By: Relevance
“…To fully identify these complex conjugates, we trapped them using mass-based SPE and subsequently obtained almost pure NMR spectra for three of them (Figure ). The SPE-NMR fraction of the C 47 H 53 O 27 isomer eluting at RT 38.11 min yielded NMR signals that were in very good agreement with those previously reported for quercetin-3- O -(2G- p -coumaroyl( trans )-3G- O -β- l -arabinosyl-3 R - O -β- d -glucosylrutinoside (Figure A). Additional 2D- 1 H COSY experiments confirmed its structure.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…To fully identify these complex conjugates, we trapped them using mass-based SPE and subsequently obtained almost pure NMR spectra for three of them (Figure ). The SPE-NMR fraction of the C 47 H 53 O 27 isomer eluting at RT 38.11 min yielded NMR signals that were in very good agreement with those previously reported for quercetin-3- O -(2G- p -coumaroyl( trans )-3G- O -β- l -arabinosyl-3 R - O -β- d -glucosylrutinoside (Figure A). Additional 2D- 1 H COSY experiments confirmed its structure.…”
Section: Resultssupporting
confidence: 89%
“…Currently, there is no single experimental database that provides all chemical knowledge of a sample, which hampers a fast identification based on a combination of observed retention time, UV absorption, MS spectra, and NMR signals. For example, the acylated quercetin tetraglycoside with observed [M – H] − mass of 1033.2827 was already identified in an oolong tea extract in 2004, but was not fully annotated in later studies, most likely due to limited structural information . We have previously shown that our HPLC-MS-SPE-NMR approach enabled structural elucidation of quercetin and kaempferol glycosides, including several isomers .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant extracts have been widely used as topical applications for wound-healing, anti-aging, and disease treatments. Teas are classified into three major categories based on how they are manufactured as follows: (a) unfermented green tea, (b) partially fermented Oolong tea, and (c) fully fermented black tea [7,8]. Catechins (EGCG) and alkaloids (caffeine), the main active ingredients in green tea, have been proven to have a variety of physiological functions, such as protecting against cancers of the duodenum, colon, skin, lung, breast, esophagus, pancreas, and prostate.…”
mentioning
confidence: 99%